A comparative analysis of repositioning of mandibular fractures using a manual method and intermaxillary traction before and during surgery - Kołciuk, Andrzej; Koch, Karol; Bętkowski, Błażej; Kołciuk, Lidia; Strużycka, Izabela; Zawadzki, Paweł (Forum Ortodontyczne / Orthodontic Forum, 2019)
Anatomical repositioning is the base for proper treatment of mandibular fractures. Bone fragments can be repositioned with intermaxillary traction placed before osteosynthesis or manually during surgery. Both methods are considered to be equal. Aim. The aim of the study was to compare the outcomes of treatment of mandibular fractures by miniplate osteosynthesis with preoperative repositioning, with the use of intermaxillary traction and only manual reduction during the procedure. Material and methods. The material included medical documentation of 319 patients treated for isolated mandibular fractures at the Department of Craniomaxillofacial Surgery, Oral Surgery and Implantology, Medical University of Warsaw. Malocclusions observed in patients immediately and one week after surgery were analysed. Moreover, a type of a mandibular fracture and method used for repositioning of bone fragments were evaluated. Results. Normal occlusion was observed in 96% of patients with intermaxillary traction and 99% patients who had not had traction placed before osteosynthesis. There were no statistically significant differences in results between both groups. Intermaxillary traction was statistically more frequently placed in case of complex fractures. Discussion. Proper osteosynthesis of a mandibular fracture can be performed without intermaxillary traction; however, in complex multifragmented fractures intermaxillary fixation is still an important part of treatment. Mini-screws introduced into the alveolar process and Ivy loops are an alternative method to standard dental splints and they are often used in clinical practice.